The Examination of the European Stone Fruit Yellow Phytoplasma (Ca. Phytoplasma Prunorum) and his Vector, Plum Psyllid (Cacopsylla Pruni) in Hungarian Apricot Orchards - Galovics, Attila; Nagyné Galbács, Zsuzsanna; Várallyay, Éva; Keresztes, Balázs (GEORGIKON FOR AGRICULTURE, 2024)
Apricot cultivation is one of the most difficult tasks in crop production and crop protection. In addition to the many risk factors (e.g. late fruit set, high manual labour requirements, short shelf life of the fruit), there are also significant plant protection problems (mainly bacterial and fungal infections). These are now being complicated by Ca. Phytoplasma prunorum. The phytoplasma disease, which causes chlorosis, defoliation and later partial and complete death, has recently been fully understood, but its control is still a future task, which should be started before planting. This would require national testing and monitoring at a level that would ensure the establishment of phytoplasma-free propagating material. The control of plum psyllid, a vector that does not cause spectacular damage, is only one segment of the necessary control solutions, which is complicated by numerous factors. Its natural food sources, such as wild Prunus species, are cosmopolites, and they can be infected by phytoplasma without causing visible symptoms. The plum psyllid spends a short period of time on wild and cultivated Prunus species, but even during this time it is able to transmit the phytoplasma that incubates persistently in it. For the assessment of phytoplasma infection, the Nucleospin Plant II kit, the Plant Material Lysis kit (for the preparation of crude extracts) and the LAMP assay for the detection of phytoplasma in plant extracts from roots, leaves and also insects gave rapid and evaluable results. The correlation between the determination of the visual infection and the actual infection is not clear, as phytoplasma was not detected in some dying specimens despite severe symptoms in the trees. The key to control is the use of controlled (phytoplasma-free) propagating material, predictive control of early settling vectors and the removal of diseased trees and rootstocks. In this essay, the results on plum psyllids are highlighted.